Methodology for determining the calculation of the standard for the number of medical visits - Palonik, Iyrina S.; Shandora, Natalia I. (Journal of the Belarusian State University. Economics, 2018)
The author оf article analyses out-patient care in the Republic of Belarus. There is considered the need for changes in primary health care to improve the efficiency of the health care system. Changes should be aimed at reducing costs and creating a model of managed care based on volume planning and resource support, taking into account the needs for medical services. There is proposed a methodology for determining the calculation of the standard of the number of medical visits, which will allow to optimize the work of outpatient clinics and fill the needs of the population for out-patient care.
Keywords: outpatient and polyclinic care; health care system; medical visits